2005
DOI: 10.1158/0008-5472.can-05-1187
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island Methylation of DNA Damage Response Genes in Advanced Ovarian Cancer

Abstract: We have determined the methylation frequencies of 24 CpG islands of genes associated with DNA damage responses or with ovarian cancer in 106 stage III/IV epithelial ovarian tumors. We have analyzed this data for whether there is evidence of a CpG island methylator phenotype or associations of CpG island methylation with response to chemotherapy in advanced ovarian cancer. Frequent methylation was observed for OPCML, DCR1, RASSF1A, HIC1, BRCA1, and MINT25 (33.3%, 30.7%, 26.4%, 17.3%, 12.3%, and 12.0%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
147
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(162 citation statements)
references
References 52 publications
9
147
3
1
Order By: Relevance
“…A fourth study by Teodoridis et al (2005) failed to detect FANCF methylation in 106 stage III and IV ovarian cancers. It is unclear whether the differences between the studies that are positive for methylation (including the present one) and that of Teodoridis are due to differences in techniques or patient populations.…”
Section: Discussionmentioning
confidence: 98%
“…A fourth study by Teodoridis et al (2005) failed to detect FANCF methylation in 106 stage III and IV ovarian cancers. It is unclear whether the differences between the studies that are positive for methylation (including the present one) and that of Teodoridis are due to differences in techniques or patient populations.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, clear cell ovarian cancers are reportedly more resistant to chemotherapy than other types (Sugiyama et al, 2000), and this difference in sensitivity may be caused in part by differences in the genes methylated in clear cell and nonclear cell tumours. In fact, Teodoridis et al (2005) reported that methylation of genes involved in DNA repair was significantly associated with response to chemotherapy, while Chan et al (2005) reported that methylation of 18S and 28S ribosomal DNA genes is associated with longer progression-free survival in ovarian cancer. Taken together, these results suggest that differences in the epigenetic signatures between clear cell and other types of ovarian cancer may be a useful diagnostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Cells deficient in BRCA1 have reduced efficiency in repairing DNA damage caused by cytotoxic agents. It has been shown that hypermethylation of the BRCA1 promoter region causes increased sensitivity to platinum drugs (Teodoridis et al 2005). Also in two ovarian cancer cell lines decreasing BRCA1 mRNA using inhibition assays correlated to increased sensitivity to platinums (Quinn et al 2007).…”
Section: Resistance Developmentmentioning
confidence: 99%